Clinical significance of cell-free DNA concentration and integrity in serum of gastric cancer patients before and after surgery - Zhang, Xueliang; Wu, Zhenfeng; Shen, Qian; Li, Rong; Jiang, Xiaohui; Wu, Jindong; Li, Ding; Wang, Ding; Zou, Chang; Zhong, Yuejiao; Cheng, Xianfeng (Cellular and Molecular Biology, 2019)
Early onset of gastric cancer (GC) is almost asymptomatic, thereby making early diagnosis and early treatment difficult. Blood samples were taken from 90 GC patients who had not undergone surgery, and from another set of 110 GC patients who had undergone surgery. The control consisted of 90 healthy individuals. Cell-free DNA (cfDNA) and its integrity were assayed using qPCR. The association between cfDNA levels and clinical presentations of GC was analyzed. In addition, cfDNA, carcino-embryonic antigen (CEA), carbohydrate antigen 724 (CA724), carbohydrate antigen 125 (CA125) and carbohydrate antigen 199 (CA199) were subjected to specificity and sensitivity analyses using ROC. The levels of cfDNA of GC patients before surgery were markedly higher than corresponding values in patients with GC after surgery. Post-surgery, the two indices were also significantly higher in GC patients than in the healthy group. The correlation between cfDNA concentration/integrity and gender, age, TNM stage, tumor differentiation, tumor location, neuronspecific enolase (NSE), or alpha fetoprotein (AFP) expression, was not significant in GC patients before or after surgery. However, the correlation between cfDNA and concentrations of CEA/CA125 was significant. The CA199 expression level was significantly correlated with cfDNA integrity. The AUC values of cfDNA concentration and integrity were higher than other tumor markers. Measurement of cfDNA concentration and integrity may be an ideal tumor screening method with higher sensitivity and specificity than traditional tumor biomarkers. The cfDNA concentration and integrity are significantly increased in plasma of GC patients, and may serve as promising indicators for GC.